Blurring the Lines Journalism and Epidemiology in the Time of Corona. Issue 1 (25th January 2022) - Alba, Sandra
Abstract: Journalism has borrowed tools and expertise from epidemiology in reporting on Covid-19. Epidemiologists should borrow from journalists too, says Sandra Alba Abstract : Journalism has borrowed tools and expertise from epidemiology in reporting on Covid-19. Epidemiologists should borrow from journalists too, says Sandra Alba.